2007
DOI: 10.1155/2007/85024
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Splitter Blades on the Flow Field of a Centrifugal Pump: Test-Analysis Comparison

Abstract: This work aims at studying the influence of adding splitter blades on the performance of a hydraulic centrifugal pump. The studied machine is an ENSIVAL-MORET MP 250.200.400 pump (diameter = 408 mm, 5 blades, specific speed = 32), whose impeller is designed with and without splitter blades. Velocity and pressure fields are computed using unsteady Reynolds-averaged NavierStokes (URANS) approach at different flow rates. The sliding mesh method is used to model the rotor zone motion in order to simulate the impel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 7 publications
1
61
0
1
Order By: Relevance
“…Pressure magnitude at 2 reaches the maximum value, and it achieves minimum value at 4 . Root mean square (RMS) method was adopted to deal with unsteady pressure signals at different computing moments in order to analyze pressure characteristics on periphery of slope volute as shown in (5). Figure 9 shows RMS values of different monitoring points at three flow rates.…”
Section: Pressure Pulsation and Rotatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Pressure magnitude at 2 reaches the maximum value, and it achieves minimum value at 4 . Root mean square (RMS) method was adopted to deal with unsteady pressure signals at different computing moments in order to analyze pressure characteristics on periphery of slope volute as shown in (5). Figure 9 shows RMS values of different monitoring points at three flow rates.…”
Section: Pressure Pulsation and Rotatingmentioning
confidence: 99%
“…Many researches have been done in order to reduce pressure fluctuation in centrifugal pump, and most of them are focusing on parameters of impeller. Some special structures of impeller have been proposed, for instance, the splitter blade [5]. However the structure of volute is rarely taken into account to reduce rotor-stator interaction.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, HR\^@XP\j^ [1] studied centrifugal pumps with different splitter blades and found that splitter blades can increase pump efficiency and head and can improve pump cavitation and noise performances. Kergourlay et al [2] simulated the internal flow of centrifugal pump with and without splitter blades. They compared the numerical results with the experiments and affirmed a positive role of the splitter blades in internal flow improvement and hydraulic performance improvement.…”
Section: Introductionmentioning
confidence: 99%
“…A splitter blade can guide flow direction along the blade passage, and especially is more effective for enhancing the pressure rise in centrifugal impeller types. Kergourlay et al [1] investigated the influence of adding splitter blades on the hydraulic performance of a centrifugal pump through experimental and computational methods. Miyamoto et al [2] studied experimentally the effects of splitter blades on the flow behaviours and characteristics in unshrouded and shrouded centrifugal impellers.…”
Section: Introductionmentioning
confidence: 99%